2021
DOI: 10.30831/akukeg.847145
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Academic Amotivation and Academic Achievement: A Study on Middle School Students

Abstract: This study aimed to determine whether academic amotivation predicts academic achievement in middle-school students. In addition, it was examined whether the students' academic amotivation levels differed by their gender. Study sample consisted of 342 eighth-grade students from middle-schools in Kahramanmaras city in Turkey. Data were collected from Academic Amotivation Inventory. A simple-linear regression analysis was utilized to examine to what extent academic amotivation accounted for variance in academic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 117 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…An individual's motivation to accomplish a task enables him/her to orient himself/herself towards that field and to work persistently in that field. Many studies have shown that student motivation and academic achievement are related (Ahmed et al, 2010;Cleary & Chen, 2009;İlter, 2021;Woolley et al, 2010).…”
mentioning
confidence: 99%
“…An individual's motivation to accomplish a task enables him/her to orient himself/herself towards that field and to work persistently in that field. Many studies have shown that student motivation and academic achievement are related (Ahmed et al, 2010;Cleary & Chen, 2009;İlter, 2021;Woolley et al, 2010).…”
mentioning
confidence: 99%